Surgical outcomes of fully endoscopic microvascular decompression with intraoperative neurophysiological monitoring - Tam, Le Duc; Ha, Duong Dai; Giang, Le Minh; Hung, Kieu Dinh; Kien, Tran Trung; Hai, Vu Trung; Tam, Nguyen Thanh; Trang, Nguyen Thi Thuy (Tạp chí Nghiên cứu Y học, 2026)
Endoscopic microvascular decompression combined with intraoperative neurophysiological monitoring has recently become an advanced technique for treating neurovascular compression syndromes in the cerebellopontine angle. This prospective cohort study included 28 patients-11 with hemifacial spasm and 17 with trigeminal neuralgia-who underwent fully endoscopic decompression at Hanoi Medical University Hospital from September 2024 to October 2025. Neurophysiological monitoring included brainstem auditory evoked potentials, brainstem trigeminal evoked potentials, lateral spread response, and the Zhong-Lee response. In the hemifacial spasm group, the mean preoperative clinical score was 14.0 ± 1.4, which improved to 0 after surgery, and the quality-of-life score decreased from 82% ± 9% preoperatively to 0% postoperatively (p < 0.001). All cases involved anterior inferior cerebellar artery compression with complete intraoperative disappearance of lateral spread responses and positive Zhong-Lee responses. In trigeminal neuralgia, 100% achieved Barrow Neurological Institute grade I pain relief at one month. Reported complications included one meningitis, four transient facial palsy, and two transient facial numbness. Fully endoscopic microvascular decompression with intraoperative neurophysiological monitoring proved to be a safe and effective surgical technique that ensures precise decompression, functional preservation, and favorable postoperative outcomes.